2021
DOI: 10.1186/s12905-021-01566-0
|View full text |Cite
|
Sign up to set email alerts
|

Women empowerment in reproductive health: a systematic review of measurement properties

Abstract: Introduction There is a considerable dearth of official metrics for women empowerment, which is pivotal to observe universal progress towards Sustainable Development Goals 5, targeting "achieve gender equality and empower all women and girls.” This study aimed to introduce, critically appraise, and summarize the measurement properties of women empowerment scales in sexual and reproductive health. Methods A comprehensive systematic literature searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
2
9
0
1
Order By: Relevance
“…When young people are empowered with information on sexual and reproductive health, they are more likely to embrace protective sexual behaviors and make healthy choices about their reproductive health [25,31]. Even though there is limited evidence on the association between sexual and reproductive knowledge and protective sexual behavior, our finding is consistent with previous studies reporting a positive association between measures of empowerment or agency and contraceptive use [32][33][34]. Our finding is consistent with studies that have reported the association between sexuality education and young people's sexual behavior [14,35].…”
Section: Discussionsupporting
confidence: 89%
“…When young people are empowered with information on sexual and reproductive health, they are more likely to embrace protective sexual behaviors and make healthy choices about their reproductive health [25,31]. Even though there is limited evidence on the association between sexual and reproductive knowledge and protective sexual behavior, our finding is consistent with previous studies reporting a positive association between measures of empowerment or agency and contraceptive use [32][33][34]. Our finding is consistent with studies that have reported the association between sexuality education and young people's sexual behavior [14,35].…”
Section: Discussionsupporting
confidence: 89%
“… 5 , 38 , 49 , 51 Although social and health factors directly influence fertility control, it is hypothesized that women's empowerment is also linked to FRH. 5 , 15 , 49 , 51 , 58 , 59 , 60 , 61 Understanding current and total fertility is essential for monitoring population growth and developing policies and programs. The fundamental drivers of population growth, namely human FRH outcomes, are influenced by various individual, household, community, national, and regional characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, a recent systematic review investigating the measurement properties of women empowerment scales in sexual and reproductive health found the most common domains explored were decision making, freedom of coercion, and communication with a partner. 19 …”
Section: Mapping Measures Of Reproductive Empowermentmentioning
confidence: 99%